DETERMINAN KINERJA KEUANGAN PEMERINTAH DAERAH DI PROVINSI SUMATERA SELATAN - Zulfalailia; Faridah; Oktarida, Anggeraini (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
The financial performance of regional governments in the regency/city of South Sumatra Province is the focus of this study, which seeks to identify the partial and simultaneous influences of regional original income, balancing funds, capital expenditures, and prosperity levels. This study makes use of secondary data derived from the Regency/City Budget Realisation Report for South Sumatra Province for the fiscal year 2018–2022, which is a part of the Regional Government Financial Report (LKPD). This study use multiple linear regression and the classical assumption test for its analysis. Research shows that (1) Original Regional Income significantly affects the financial performance of regional governments in a good way. (2) When it comes to the budgetary performance of regional governments, Balancing Funds are a major factor. (3) The financial performance of regional governments is unaffected by capital expenditures. (4) The fiscal health of municipalities is positively correlated with the degree of prosperity. There is a strong and substantial relationship between the level of prosperity, regional original income, balancing funds, capital expenditures, and regional government financial performance.